2007
DOI: 10.1007/s00442-007-0846-4
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the role of individual species for overyielding in experimental grassland communities composed of potentially dominant species

Abstract: Several studies have shown that the contribution of individual species to the positive relationship between species richness and community biomass production cannot be easily predicted from species monocultures. Here, we used a biodiversity experiment with a pool of nine potentially dominant grassland species to relate the species richness-productivity relationship to responses in density, size and aboveground allocation patterns of individual species. Aboveground community biomass increased strongly with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 59 publications
(69 reference statements)
6
83
0
5
Order By: Relevance
“…Richness effects may be dependent on the duration of the experiment. In accordance with the present study, short-term terrestrial grassland experiments have not found a relationship between species richness and primary production (Naeem et al 1996, Weigelt et al 2007, while positive correlations have emerged from long-term studies (Hector et al 1999, Roscher et al 2007. Since the production of previous years may alter long-term patterns in plant communities, short-term experiments may fail to detect species complementarity (Hooper & Dukes 2004).…”
Section: Species Interactions Among Rooted Macrophytessupporting
confidence: 40%
“…Richness effects may be dependent on the duration of the experiment. In accordance with the present study, short-term terrestrial grassland experiments have not found a relationship between species richness and primary production (Naeem et al 1996, Weigelt et al 2007, while positive correlations have emerged from long-term studies (Hector et al 1999, Roscher et al 2007. Since the production of previous years may alter long-term patterns in plant communities, short-term experiments may fail to detect species complementarity (Hooper & Dukes 2004).…”
Section: Species Interactions Among Rooted Macrophytessupporting
confidence: 40%
“…Thus, our 389 additional experiment complements the so-called "dominance experiment" in the framework 390 of the Jena Experiment. In contrast to our additional experiment, the species pool for the 391 "dominance experiment" was selected on the criterion to consist of potentially dominant 392 species in semi-natural grasslands of the study region (Roscher et al 2004), but these species 393 showed different levels of monoculture productivity (Roscher et al 2005(Roscher et al , 2007. 394…”
Section: Discussion 383mentioning
confidence: 99%
“…Here, we observed the presence of the plant functional groups of tall herbs and legumes to contribute the largest proportion to overall community infection. As they were among the dominant plant species in mixtures with high biomass contributions (Roscher et al 2007, Marquard et al 2009b, we assume them to be easily exposed to inoculum rain. In addition, they are effectively shielding smaller neighboring plant species from their associated pathogens, thus reducing pathogen presence and incidence for understory species in diverse communities.…”
Section: The Role Of Host Functional Group Identity For Pathogen Presmentioning
confidence: 99%
“…While nitrogen fertilization has been demonstrated to increase pathogen severity, the effect size varies, and depends on host characteristics, pathogen identity, and season (Hatcher and Paul 2000, Han et al 2008, Newton et al 2010. The presence of legumes as a nitrogen-fixing plant functional group can also increase within-plant nutrient status and nutrient availability for neighboring plant species within communities (Spehn et al 2002), thus altering nutritional levels and growth structure through increased leaf area of neighboring plant species (Roscher et al 2007, Marquard et al 2009a, b, Schmidtke et al 2010. We observed the 60 species mixtures where both tall herb and legume species are present to have the lowest pathogen incidence and severity.…”
Section: The Role Of Host Functional Group Identity For Pathogen Presmentioning
confidence: 99%